Physiological and pathophysiological factors affecting the expression and activity of the drug transporter MRP2 in intestine: impact on its function as membrane barrier - Arana, Maite Rocío; Tocchetti, Guillermo N.; Rigalli, Juan Pablo; Mottino, Aldo D.; Villanueva, Silvina S. M. (Pharmacological research, 2016)
The gastrointestinal epithelium functions as a selective barrier to absorb nutrients, electrolytes and water, but at the same time restricts the passage into the systemic circulation of intraluminal potentially toxic compounds. This epithelium maintains its selective barrier function through the presence of very selective and complex intercellular junctions and the ability of the absorptive cells to reject those compounds. Accordingly, the enterocytes metabolize orally incorporated xenobiotics and secrete the hydrophilic metabolites back into the intestinal lumen through specific transporters localized apically. In the recent decades, there has been increasing recognition of the existence of the intestinal cellular barrier. In the present review we focus on the role of the multidrug resistance-associated protein 2 (MRP2, ABCC2) in the apical membrane of the enterocytes, as an important component of this intestinal barrier, as well as on its regulation. We provide a detailed compilation of significant contributions demonstrating that MRP2 expression and function vary under relevant physiological and pathophysiological conditions. Because MRP2 activity modulates the availability and pharmacokinetics of many therapeutic drugs administered orally, their therapeutic efficacy and safety may vary as well.
Gesehen am 18.08.2020